GOING CONCERN OPINION IN PROVIDING INFORMATION FOR THE MARKETS - Bambang Hartadi (Universitas Hayam Wuruk Perbanas, 2012)
Audit opinion theoretically should be used as a good early warning by the investors. This istrue, especially, because the going concern opinion should provide the real company performancethan can be used by the market to predict the ability of company to keep their goingconcern operation. From such reasons, this study analyzes whether the going concern opinion(GCO), provides useful information about the value of the firm for other parties, especiallythe market. In this study, the samples were selected by using purposive samplingmethod of manufacturing companies in LQ45. In testing the hypothesis, the researcher usesmultiple linear regressions. In some cases, the results do not support previous studies. GoingConcern Opinion and Net Income do not affect the Market Value of Equity. Thus, it does notsupport the previous research findings. On the contrary, the Book Value of Equity andgrowth have significant effect on the Market Value of Equity, in which this supports the previousones.